Healthcare professionals’ awareness of the levels of disciplinary collaboration in older adults’ care during clinical practice in Nigeria: A multi-method study - Chukwunonso Geoffrey Okafor; Augustine Chukwuebuka Okoh; Adaobi Odega; Stanley Maduagwu; Michael Kalu (PLoS ONE, 2026)
Introduction Collaborative care has been recognized as a fundamental aspect of geriatric/gerontological care, as it can enhance health and social outcomes among older adults. However, very little is known about Nigerian healthcare professionals’ (HCPs) awareness of disciplinary collaborations in older adults’ care. This study investigated the HCPs’ awareness (level of awareness, definitions, and perceived practice) of the disciplinary collaborations in older adults’ care during clinical practice at a tertiary hospital in the South-Eastern region of Nigeria. Methods We conducted a multi-method study involving 245 HCPs who responded to authors’ developed questionnaire. Data was analyzed using descriptive and inferential statistics. Results The level of awareness of disciplinary collaboration varies: intradisciplinary (65.7%), multidisciplinary (72.1%), cross-disciplinary (57.1%), interdisciplinary (76.3%), and transdisciplinary (40.8%) collaborations. Having a Bachelor’s degree (OR = 1.055, 95% CI [−0.154, 5.662], p = 0.038) and a transdisciplinary education (OR = 1.023, 95% CI [0.904, 6.646], p = 0.010) predicted better awareness of the inter-/trans]disciplinary collaborations. There was a significant change in the participants’ level of awareness of the type of disciplinary practice in their hospital before and after seeing the description of the collaborative practice constructs [ X 2 (2)=29.747, p < 0.001]. Barriers to higher collaborative practices in geriatric/gerontological care were inequitable remuneration ( X 2 (2) = 4.332, p = 0.037), lack of integrated electronic medical records ( X 2 (2) = 12.562, p = 0.002), and a limited number of specialists ( X 2 (2) = 54.093, p < 0.001). Conclusion Achieving consensus on the definition of intra-, cross-, multi-, inter-, and transdisciplinary practice is essential for a clear understanding of the constructs, facilitating its proper implementation in geriatric care and the development of effective solutions to systemic barriers. A transdisciplinary educational curriculum could support the uptake of transdisciplinary collaborative geriatric practice models in Nigeria.